Forbidden fruit : a Corinna Chapman mystery - Greenwood, Kerry (Greenwood, Kerry. Corinna Chapman mystery., 2010)
With the help of a troupe of free-spirited freegans, three very clever internet hackers and a bunch of singing vegans, Melbourne baker Corinna and her luscious Daniel go head-to-head with a sinister religious cult on a mission and a band of Romanies out for revenge in a wild and wonderful chase to find two missing runaways.